Indonesia’s forest moratorium: A stepping stone to better forest governance? - Murdiyarso, Daniel; Dewi, S.; Lawrence, D.; Seymour, F. (Center for International Forestry Research, 2011)
On 20 May 2011, the government of Indonesia released Presidential Instruction No. 10/2011 on ‘The postponement of issuance of new licences and improving governance of primary natural forest and peatland’, as part of Indonesia’s cooperation with the government of the Kingdom of Norway, according to the Letter of Intent signed by the two governments on 26 May 2010. The Presidential Instruction, which effectively imposes a 2-year moratorium on new forest concession licences, generated widespread public discourse and important policy implications. This working paper analyses the significance of the moratorium in the context of improving forest governance in Indonesia. The moratorium on new concessions in forest areas is an important step towards meeting Indonesia’s voluntary commitment to reduce emissions. However, several issues are unresolved concerning the area and status of land covered by the moratorium, and hence the amount of carbon stored in the affected forests and peatlands. The moratorium should be seen as the means and breathing space to establish enabling conditions to reduce greenhouse gases emissions, improve forest and peatland governance, for when a global mechanism such as REDD+ is fully implemented. It could pave the way for successful policy reform far beyond its 2-year term.